Running with Expanding Heart : Meeting God in Everyday Life - Reuter, Mary (Book collections on Project MUSE., 2010)
Mary Reuter recalls how, as a child taking piano lessons, she often skipped practicing scales and thought her teacher would not notice. Reuter admits she never did advance to the level of a skilled pianist. But in Running with Expanding Heart readers will discover that she is well practiced, and thus skilled, in paying attention to the extraordinary in the ordinary, in discovering the presence of God in the events of daily life. Through Reuter's poignant and humorous stories, and through her careful listening to Scripture and the Rule of Benedict, readers will also take up the practice of looking for God in unexpected places, and in doing so they will find their hearts expanding with the unconditional and all-embracing love of God.